The Evaluation of Psychosexual Profiles in Dominant and Submissive BDSM Practitioners: A Bayesian Approach - Daniele Mollaioli; Tommaso B. Jannini; Diana Piga Malaianu; Andrea Sansone; Elena Colonnello; Erika Limoncin; Giacomo Ciocca; Emmanuele A. Jannini (Sexes, 2025)
Bondage/discipline, Dominance/submission, Sadism/Masochism (BDSM) is a multifaceted spectrum of consensual sexual practices, that has long intrigued the psychological community for its implications on mental health and personality. While previous research has shed light on its psychopathological aspects, less is known about the distinct psychosexual dimensions that characterize individuals who assume dominant or submissive roles within these dynamics. Our research aims to identify differences in personality traits between dominant and submissive individuals and explore the relationship between BDSM roles and mental health outcomes. While previous studies have explored personality traits in BDSM practitioners, research specifically examining the associations between BDSM roles and multiple psychological constructs remains limited. To address this, we employed Bayesian methods with non-informative priors, including ANOVA and linear regression, to evaluate the associations between self-identified BDSM roles and psychological constructs with the specific intent to build informative priors for future research. A sample of 99 BDSM practitioners from online forums participated, providing responses across several psychometric instruments. The study utilized comprehensive psychometric evaluations, including the Big Five Inventory for personality assessment, the Hypersexual Behavior Inventory for hypersexuality, the Brief Sensation Seeking Scale for sensation seeking, the Patient Health Questionnaire for depression, and the General Anxiety Disorder scale for anxiety. Bayesian regression analysis revealed that dominant practitioners exhibit lower hypersexuality and agreeableness, while submissive practitioners show higher levels of agreeableness, depression, hypersexuality, and sensation seeking. These findings highlight distinct psychosexual profiles associated with BDSM roles and provide several implications for mental health professionals working with BDSM practitioners, emphasizing the need to assess and address underlying psychological factors. Future research should further explore these psychosexual dynamics to develop targeted interventions for enhancing psychological well-being and relationship satisfaction within the BDSM community.